An Analysis of Illocutionary Acts of The Main Characters Shown in The Nun Movie (2018) - I Wayan Yogi Astrawan; Ni Ketut Alit Ida Setianingsih; I Nyoman Arya Wibawa (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This paper explores the illocutionary acts performed by the main characters in the 2018 movie "The Nun," directed by Corin Hardy. The study focuses on Sister Irene and Father Burke, examining their dialogues to identify and analyze the types and meanings of illocutionary acts based on Austin's speech act theory. This research used a qualitative research method, the thesis investigates how the characters' utterances convey specific meanings and intentions within the context of the film's narrative. The technique of data collection in this research was collected by downloading the movie script, watching the movie, reading the dialogue in movie script, taking notes and collecting the data in table in order to make the writer is easier in analyzing the illocutionary acts. The analysis reveals various types of illocutionary acts, such as verdictives, exercitives, commissives, expositives, and behabitives, and discusses their implications in the movie's context. This research contributes to a deeper understanding of language use in cinematic dialogues and provides insights into the pragmatic aspects of character communication in film.